Linear Growth in Pediatric Kidney Transplant Population - Lopez-Gonzalez, Mercedes; Munoz, Marina; Perez-Beltran, Victor; Cruz, Alejandro; Gander, Romy; Ariceta, Gema (Frontiers in Pediatrics, 2020)
Introduction: Growth retardation is one of the main complications of chronic kidney disease (CKD) in children and induces a negative impact on quality of life. Materials and Methods: Retrospective analysis of all consecutive patients younger than 18 years old who received a first KT in our center between 2008 and 2018. Results: 95 first KT recipients, median age at KT of 7.83 years. At the time of KT, 65.52% of males and 54.05% females showed normal height. After transplantation, linear growth improved from −1.53 at transplant to −1.37 SDS height at the last visit. We detected a different linear growth pattern according to patient age at KT. Children younger than 3 years old exhibited the most significant growth retardation at baseline and the greatest linear growth over time (−2.29 vs. −1.82 SDS height), whereas catch-up was not observed in older patients. Multivariate analysis showed that use of corticosteroids was negatively related to SDS height at 1 year after transplantation and final SDS height only was positively associated with SDS height at KT. 44.2 and 22.1% patients received rhGH treatment before and after KT. 71.88% patients reached adulthood with normal final height. Conclusions: In our study, pediatric KT recipients exhibited a normal height in more than half of cases at KT and in more than two thirds at the final adult height. Only children younger than 6 years old presented a relevant growth catch-up after KT. Treatment with rhGH was used before and after KT with significant improvement in height.